Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Tiket Online Pada Traveloka - Yoeliastuti, Yoeliastuti; Widowati, Retno; Badriyah, Badriyah (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
This study aims to determine what factors influence the decision to purchase tickets online at Traveloka. The public's need for transportation is so high, especially in the era of the covid 19 pandemic. The limited space for people to carry out activities requires people to carry out activities online. In marketing activities, brand image and price become a reference for people to make purchases. For this reason, the company is expected to be able to improve public services and convenience in transacting through brand image and pricing.  This study uses quantitative methods with a population of 78 consumers. The distribution of questionnaires is done by using google forms to make it easier to get consumer data. The results of the F test are known that the calculated F value is 191.704 > F table 3.15, which means that there is a significant influence between brand image and price on purchasing decisions. Multiple linear regression value obtained Y = 3.440 + 0.171 X1 + 1.442 X2 where the most influential variable on purchasing decisions is the price variable.